A Mixed-chimerism Protocol Utilizing Thymoglobulin and Belatacept Did Not Induce Lung Allograft Tolerance, Despite Previous Success in Renal Allotransplantation. Issue 6 (25th May 2021) - Sommer, Wiebke; O, Jane M.; Pruner, Kurt B.; Dehnadi, Abbas; Ha Huh, Kyu; Robinson, Kortney A.; Hanekamp, Isabel; Rosales, Ivy; Bean, Alison S.; Paster, Josh; Oura, Tetsu; Neal Smith, Rex; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: In kidney transplantation, long-term allograft acceptance in cynomolgus macaques was achieved using a mixed-chimerism protocol based on the clinically available reagents, rabbit anti-thymocyte globulin (ATG), and belatacept. Here, we have tested the same protocol in cynomolgus macaques transplanted with fully allogeneic lung grafts. Methods: Five cynomolgus macaques underwent left orthotopic lung transplantation. Initial immunosuppression included equine ATG and anti-IL6RmAb induction, followed by triple-drug immunosuppression for 4 mo. Post-transplant, a nonmyeloablative conditioning regimen was applied, including total body and thymic irradiation. Rabbit ATG, belatacept, anti-IL6RmAb, and donor bone marrow transplantation (DBMT) were given, in addition to a 28-d course of cyclosporine. All immunosuppressant drugs were stopped on day 29 after DBMT. Results: One monkey rejected its lung before DBMT due to AMR, after developing donor-specific antibodies. Two monkeys developed fatal post-transplant lymphoproliferative disorder, and both monkeys had signs of cellular rejection in their allografts upon autopsy. The remaining 2 monkeys showed severe cellular rejection on days 42 and 70 post-DBMT. Cytokine analysis suggested higher levels of pro-inflammatory markers in the lung transplant cohort, as compared to kidney recipients. Conclusion: Although the clinically applicable protocol showed success in kidney transplantation, the study did not show long-term survival in a lung transplant model, highlighting the organ-specific differences in tolerance induction.